INDIVIDUAL-AND GROUP-BASED INTERSPECIFIC COMPETITION BETWEEN ALIEN INVASIVE PLANT ERIGERON ANNUUS AND TWO CO-EXISTING HERBS - Ai-Ming Cai; Yi-Gang Song; Asad Shabbir; Xin He; Rong Yan; Hui Yan; Lie Xu; Wei He; Zhuo-Wen Zhang; Yong-Jian Wang1 (Journal of Animal and Plant Sciences, 2017)
Individual- and group-based interspecific competition played the important role on growth and distribution of invasive plant species and further influenced growth and diversity of plant communities. However, none has examined the both effects of interspecific competition on a worst alien invasive plant Erigeron annuus. In the greenhouse experiments, seedlings of invasive plant E. annuus and two co-existing herbs (a native herb Artemisia indica and a common crop Ipomoea batatas in the farmland) were subjected to the individual-based (without and with interspecific competition) and group-based competition [i.e. without and with interspecific competition under two distribution types(aggregation and segregation) of E. annuus]. Individual-based interspecific competition significantly affected aboveground mass, belowground mass and biomass of native A. indica and I. batatas, but did not affect growth of invasive E. annuus. Interspecific relative competition intensity (RCI) of aboveground mass and biomass mass were significantly lower in E. annuus than those in other two co-existing species. Group-based interspecific competition significantly decreased all growth measures of E. annuus. Under the segregation distribution, aboveground mass and biomass of E. annuus were significantly greater in the no competition than in the competition treatments, but was statistically the same between two competition treatments under the aggregation distribution. Moreover, RCI of biomass in E. annuus was significantly lower under the aggregation than under the segregation distribution. Therefore, E. annuus has high individual-based competitive ability, and aggregation distribution of E. annuus can increased the group-based interspecific competitive ability with two co-existing herbs.
Keywords: Erigeron annuus; plant invasion; interspecific competition; aggregation distribution; relative competition intensity